Incidence of injuries and associated factors at the senior inter provincial field hockey tournament - Pereira, Nicholas Samora (Department of Health and Rehabilitation Sciences, 2022)
Background Field Hockey is an Olympic sport that is played widely across the world at various levels. In South Africa, it is a growing sport with increasing participation for both males and females. It is a high-speed team sport, consisting of short bursts of sprinting with technical coordination of a stick and ball, as well as the tactical execution of a coach's game plan. Participation in sports, including field hockey, comes with an accepted risk of injury; however, within the team setting it can have several implications for the individual: their health, physical performance, and psychological state, both immediately and in the long term. Despite injury incidence in other team sports being well-documented, there is limited research in field hockey generally, and injury incidence and associated risk factors in South African field hockey specifically. Aim The aim of the present study was to determine the incidence of injury and associated factors amongst players participating in the 2018 South African men's and women's inter provincial field hockey tournament. Objectives The specific objectives of the study were to determine (at the 2018 men's and women's senior field hockey seven-day inter provincial tournament in South Africa): • the incidence of injury amongst players; • the burden of acquired sport injuries defined by time loss and medical attention; • the associative factors related to injury (i.e. coaching qualifications, presence of medical staff, and other non-modifiable risk factors); and • the injury incidence, injury burden and distribution of anatomical injuries between males and females. Methods The study had a descriptive, longitudinal design. All players and coaches attending the 2018 South African Hockey Association men's and women's IPT were invited to enrol in the study and were recruited prior to the start of the respective tournament periods. All the attending players participate in senior field hockey, either for club or university teams in their province. Each provincial hockey union selects their best available team of players to represent them at the inter provincial tournament which comprises of three sections. Only the teams participating in the “A” sections were eligible for recruitment into the study. The female tournament was hosted in Durban during May of 2018 and the male tournament was hosted in Pietermaritzburg in August of 2018. Participants were excluded if they were under 18 years of age or did not provide informed consent. Enrolled coaches and players were asked to complete a self-reported questionnaire. Players information was used to gather the provincial team, playing position and previous injury history. Coaching information was used to gather the educational level, years of experience and the resources available to coaches. Players were additionally asked to independently complete daily injury report forms on all seven tournament match days. This was used to collect information on injury incidence and nature, medical attention required, and time loss during the tournament week. Results Two hundred and seventy-two players (133 females; 139 males) and 22 coaches took part in this study. All injury incidence was found to be 99.5 (95% CI: 71.9 – 127.1) injuries per 1000 player match hours for males and 77.9 (95% CI: 47.1 - 108.1) injuries per 1000 player match hours for females. The incidence of medical attention injuries was 70.3 (95% CI: 46.1 – 94.4) injuries per 1000 player match hours for males, and 51.9 (95% CI: 32.3 – 71.5) injuries per 1000 player match hours for females. The incidence of time loss was 7.5 (95% CI: -0.7 – 15.75) injuries per 1000 player match hours for males, and 4.3 (95% CI: 1.04 – 9.7) injuries per 1000 player match hours for females. A large portion of injuries affected the lower extremity, accounting for 69% of injuries in male players and 70% of injuries in female players. There were no significant relationships between injury incidence and the availability of team medical support staff, coaches' education level, coaches South African Hockey Association (SAHA) level, or coaches' first aid qualifications respectively. However, players with coaches who had a Federation of International Hockey (FIH) qualification had lower injury incidence rates compared to players with coaches who did not hold this qualification (p = 0.015; Fisher exact), with a lower incidence of injury in players coached by a FIH qualified coach (logistic regression analysis p = 0.054). Players who reported previous injuries within the last 12 months were 3.5 times more likely to sustain an injury during the tournament, compared to players with no previous injury history (p < 0.0001). Female players were 2.4 times more likely to seek medical attention compared to male players (p = 0.046). There was a statistically significant association between players reporting previous injury (within the past two years) and injury during the tournament (p < 0.0001), with players who had a previous injury being 5 times more likely of sustaining an injury during the tournament. Conclusion To our knowledge, this was the largest observational study conducted in South African field hockey that included both male and female players. High incidence rates of all injuries and medical attention injuries were identified, however, the incidence of time loss injuries was much lower in comparison to existing literature. It is possible that players continue to participate in matches despite injuries requiring medical attention, that medical support staff may not limit match participation for injured players adequately, or that players seek reassurance from medical support staff for minor injuries. The findings support the existing literature reporting that the lower extremity experiences the largest amount of injuries reported by field hockey players. In the present study, the lower extremity was affected in 69% of all injuries reported in the male tournament, and in 70% of all injuries in the female tournament. In addition, previous injury history was identified as a significant risk factor for injury, which is aligned with findings from injury monitoring studies of different team sports. The findings of this study highlight the need for consensus on injury definitions in field hockey. Further research is critical to determine injury prevention strategies for male and female field hockey players.